Bay Leaf Juice (Syzygium Polyanthum) And Lavender Leaf Juice (Lavandula Angustifolia) As Ae. Aegypti Adult Mosquito Control - Pakpahan, Eka Lolita Eliyanti; Pane, Putri Yunita (Universitas Prima Indonesia, 2024)
Dengue fever cases in Indonesia, with a total of 71,633 cases as of July 2020, where Medan City experienced a 20% increase in cases in 2020. The main vector of dengue fever is Ae. Aegypti, usually prefers to suck human blood rather than animals (arthrophilic) and is usually active during the day. One way to control Ae. Aegypti mosquitoes is to break the mosquito life cycle by using insecticides. Reports from the Medan City Health Office and several studies have found an increase in cases due to the resistance of Ae. Aegypti mosquitoes to chemical insecticides. This resistance prevents mosquitoes from dying but has an impact on public health. People tend to use insecticides with the active ingredient Cypermethrin, which if used for a long time can cause problems with the upper respiratory tract, skin and eye irritation. Therefore, natural insecticides are needed that are relatively safe for humans and environmentally friendly, such as bay leaf juice (Syzygium Polyanthum) and Lavender Leaf Juice (Lavandula Angustifolia). The purpose of this study was to obtain a natural insecticide formula that can be found in the community environment and can be used by the community because it is cheap, easy and efficient and does not interfere with public health. This type of research is experimental, with the design of The Post Test Only Controlled Group Design. The population in this study was Ae. Aegypti mosquitoes located in the Jalan Durung area of ​​Medan City. The sample in this study was 20 adult Ae. Aegypti mosquitoes in each of the 3 treatments and 2 controls, namely negative control (Aquades) and positive control (Cypermethrin) totaling ± 640. The results of the study that have been obtained are that there is a statistically significant effect on the number of mosquitoes that died between the Bay Leaf Juice (Syzygium Polyanthum) group and the Lavender Leaf Juice (Lavandula Angustifolia) group. Keywords: Ae. Aegypti; Insecticide; Bay Leaf (Syzygium Polyanthum); Lavender Leaf (Lavandula Angustifolia).